801 EFFECTIVENESS OF HEARING REHABILITATION FOR CARE HOME RESIDENTS WITH DEMENTIA: A SYSTEMATIC REVIEW. (8th March 2022) - Cross, H; Dawes, P; Hooper, E; Armitage, C J; Leroi, I; Millman, R E
Abstract: Introduction: Hearing loss is common among people with dementia living in long-term care homes, leading to poorer quality of life, communication difficulties and exacerbated dementia-related symptoms. Hearing rehabilitation may improve outcomes; however, evidence suggests hearing is poorly managed in care homes. Methods: A systematic review reporting on the effectiveness of, and barriers and facilitators to, hearing rehabilitation for residents with dementia was conducted. No restrictions on publication date or language were set and grey literature was considered. Eligible studies were critically appraised and presented via a narrative review. Results: Sixteen studies, most of low-to-moderate quality, were identified. Hearing rehabilitation, including hearing devices, communication techniques and visual aids (e.g. flashcards), were reported to improve residents' communication, quality of life and reduce agitation, with improvements in staff knowledge of hearing loss and job satisfaction. Residents' symptoms of dementia presented barriers, e.g. losing or not tolerating hearing aids. Low staff prioritization of hearing loss due to time-pressures and lack of hearing-related training for staff were further barriers, particularly for residents who required assistance with hearing devices. Adopting a person-centered approach based on residents' capabilities and preferences and involving family members facilitated hearing device use. Conclusions: Residents with dementia can benefit from hearing rehabilitation. Identifying and implementing efficient, individualized hearing rehabilitation is necessary for those with complex cognitive needs. Increased funding and support for the social care sector is required to address systemic issues that pose barriers to hearing rehabilitation, including time-pressures, lack of training for staff and access to audiology services for residents.